Penalty success in professional soccer: a randomised comparison between imagery methodologies - Rhodes, J.; May, J.; Booth, A. (Journal of Imagery Research in Sport and Physical Activity, 2020)
Objectives The PETTLEP model is one of the most cited forms of imagery training to enhance sporting performance, but there is limited evidence for its long-term effectiveness and it is often compared to non-imagery controls rather than other imagery techniques. We compared PETTLEP with an imagery-based behavioural change intervention, Functional Imagery Training (FIT), and assessed long-term effectiveness for enhancing professional soccer player`s penalty kick taking. Methods Thirty male professional soccer players conducted a group goal setting task, were introduced to imagery, then randomly assigned to three conditions; individual PETTLEP, group-based FIT, or a control. Baseline penalty kick success was measured, then interventions commenced lasting for a week after which, penalties were conducted again. Penalties were conducted for a third time between 15 and 17 weeks after baseline measurements. Results There were no differences in baseline scores between conditions on vividness of imagery and penalty kicking. Whilst the control condition did not improve, both imagery conditions improved penalty performance after one week, as did their vividness of imagery scores. However, after 15 weeks, only the FIT for groups condition maintained improvements on penalty scores and PETTLEP returned to baseline. Conclusions Imagery is effective in improving penalty kick taking, but PETTLEP does not support long-term change, whereas the motivational approach of FIT does.